Window Width Estimation And The Application Of The Windowed Wigner-Ville Distribution In The Analysis Of Heart Sounds And Murmurs - Sha'ameri, Ahmad Zuri; Salleh, Sh-Hussain (2000)
This paper looks at the analysis of heart sounds and murmur using time-frequency signal analysis. The techniques used are the Wigner-Ville distribution (WVD) and windowed Wigner-Ville distribution (WWVD) that belonged to the bilinear class of time-frequency distribution. These techniques developed to provide high-resolution time-frequency representation for time-varying signals. Due the nonlinear operation involved, interference terms are introduced in the time-frequency representation. The signals of interest are modeled as multicomponent signals and the characteristics of the signal in time-lag plane are observed. From the time-lag plane, the interference components are identified, and the appropriate window width is selected in the WWVD to remove the interference. Analysis results show that WWVD produces more accurate time-frequency representation compared to the WVD and the signal-to-interference is used to quantify the improvement